PENGEMBANGAN BUKU KESIAPSIAGAAN BENCANA UNTUK SEKOLAH INKLUSI (Hasil Analisis Sekolah Ramah Anak Di Sleman Yogyakarta) - Luqman Hidayat (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2020)
AbstractNatural disaster preparedness is a concern in Indonesia, including in the world of education. The Disaster Preparedness School Program, Child Friendly Schools, Disaster Response Schools, Disaster Resilient Schools are some of the scenarios carried out by the government to prepare everything in the event of a disaster in the educational environment. Students in the educational environment are vulnerable elements in a disaster. Especially for those students with special needs. The purpose of this study is the development of a disaster preparedness book product for inclusive schools. Strategies or special ways for disaster preparedness must be considered according to the needs and characteristics of each student with special needs. The method used is research and development. The results of this study are increasing the competence of students in the attitudes and measures / knowledge of mitigation, school residents should be trained in dealing with disaster emergencies, and books developed further emphasize the concern for students with disabilities in disaster response in inclusive schools.Keywords: disaster preparedness, child friendly schools, inclusion, yogyakarta